Exploring the association between asthma and chronic comorbidities: impact on clinical outcomes - Listyoko, Aditya Sri; Okazaki, Ryota; Harada, Tomoya; Inui, Genki; Yamasaki, Akira (Frontiers in Medicine, 2024)
Asthma remains a significant global health challenge. While both the incidence and mortality rates have shown a decline, older individuals with asthma exhibit not just more severe symptoms but also demonstrate an elevated mortality rate. This phenomenon could be attributed to the presence of chronic comorbidities that exert an influence on clinical outcomes among adult patients with asthma. This review aims to present various aspects of asthma comprehensively, including the prevalence, incidence, mortality rates, and causes of death in adult patients with asthma. Additionally, this review delves into the impact of chronic comorbidities that contribute to the morbidity and mortality of patients with asthma on a global scale, encompassing conditions such as chronic kidney disease, diabetes mellitus, lung cancer, obesity, and cardiovascular disease, concerning asthma. Furthermore, the manuscript reviews the distinctions between asthma and asthma chronic obstructive pulmonary disease overlap and adds perspective on asthma as an occupational lung disease. Thus, this review aims to enhance clinicians' awareness of the significance of chronic comorbidities in the management of patients with asthma. It seeks to provide insights that contribute to a more comprehensive approach to managing patients with asthma who also have comorbid conditions.